Digital Transformation Affecting Sustainable Development: A Case of Small and Medium Enterprises during the Covid-19 Pandemic - Nga Phan Thi Hang; My Linh-Thi Nguyen; Thi Thuy Hang Le (Emerging Science Journal, 2023)
Vietnam's economy faces many difficulties and complicated developments. To create an environment with favorable conditions for sustainable development, it is necessary to have innovative business solutions that not only bring profits for businesses but also solve environmental and social problems. In addition, small and medium enterprises (SMEs) have made many positive contributions to economic restructuring, creating stable jobs for hundreds of thousands of employees and ensuring social security. Besides, SMEs in Vietnam have faced many difficulties and challenges during the COVID-19 pandemic. Thus, the papers' objectives explored critical factors affecting the sustainable development of SMEs in Vietnam. The authors applied two methods, such as qualitative and quantitative, with data obtained from 400 managers of small and medium enterprises and used structural equation modeling and SPSS 20.0, Amos software. The article's findings have the digital transformation factor's most substantial impact on sustainable development. The article's novelty is determined by five factors: market trends, state support policy, social responsibility, quality of human resources, and digital transformation. Finally, the authors recommended guidelines to help businesses be more cohesive in removing difficulties and solving issues related to credit relations to put capital into modern technology investment to ensure business effectiveness and sustainable development for SMEs. Doi: 10.28991/ESJ-2023-SPER-017 Full Text: PDF